Understanding changes in youth offenders’ risk profiles: a Latent transition analysis - Xu, Xuexin (Youth violence and juvenile justice, 2020)
This study examined youth probationers’ risk profiles at the start and the end of probation and the types of transition in risk profiles over time. It further identified the association between the transition types, their adverse family background as well as their probation completion status. Using a sample of 935 youth probationers in Singapore, a latent transition analysis was conducted based on seven dynamic domains captured in the Youth Level of Service/Case Management Inventory 2.0. Based on the risk profiles, three subgroups of youths were identified: (1) the “De-escalators” had reduced risk in one or multiple domains; (2) the “Persistors” continued to have moderate risk in most domains; and (3) the “Escalators” showed an increase in risk levels in one or multiple domains. Compared to the De-escalators, the Persistors and Escalators were less likely to complete their probation orders. Further analysis revealed that youths from nonintact families or families with conviction history showed higher relative risk in being Persistors. These findings contribute to our understanding on the changes in probationers’ risk profiles over time and provide information for early and more targeted intervention efforts.